Ação Direta: A Via Para A Transformação Social, São Paulo (1906-1919) - Marcelino, Danillo Rosa [UNIFESP] (2018)
In This Work We Seek To Analyze How The Anarchist Principle Of Direct Action Was Mobilized By The Workers In The Brazil Between 1906 And 1919. The Regional Focus Is Centered At São Paulo Town; However, We Are Not Limited To It. Likewise, We Will Explore Also An Analyze With Transnational Perspective. Our First Step Is To Understand When Appeared The Direct Action And Which Was The Mean Given To It By Theorists. After, We Try To Observe How In Alliance With The Anarchists And Revolutionary Sindicalists The Workers At São Paulo Town To Mobilize The Anarchist Principle. Following, Our Intention Is To Observe That Mobilization Of Direct Action In Brazil And In World. Our Aims Are To Understand How The Idea Of Direct Action Circulated Inside Of A Heterogeneous Transnational Movement And Contributing With The Thought Anarchist.